Pragmatic Functions of Discourse Particles in Lutsotso conversations - Joel Ongolo; Benard Mudogo; David Barasa (UIN Salatiga, 2024)
The study of the functions of discourse particles in the African languages has received much attention from various scholars, although not from a pragmatic perspective. A good understanding of the pragmatic functions of discourse particles in African languages can benefit language users. However, limited knowledge in this field has affected communication of ideas more clearly and concisely. This paper explores the pragmatic functions of these discourse particles in Lutsotso conversations within the Relevance Theory (RT) structure by Sperber and Wilson (1995). A combined method of native speakers’ intuition and data extraction from Lutsotso conversations were used to collect data. After that, a descriptive research design was used to analyze the collected data. The findings revealed that in Lutsotso conversations, discourse particles play the following pragmatic functions depending on the context: cutting in politely, initiating a new topic, highlighting of a hypothesis that immediately follows, capturing the attention of the listeners, holding the flow and keeping one’s turn, and disagreeing politely.